EVALUASI EFEKTIVITAS PROGRAM SHORT COURSE MANAJEMEN SUMBERDAYA MANUSIA MELALUI PROGRAM COLLABORATIVE ONLINE INTERNATIONAL LEARNING IPB UNIVERSITY DAN UMS - Fedro Agusti Constantin; Lindawati Kartika (Jurnal Ilmiah Wahana Pendidikan, 2023)
The basics of human resource management are important for students who are about to enter the world of work. COIL Course: Fundamentals of Human Resources Management (HRM) as one of the Virtual Exchange activities provides students with an understanding of material about HRM. The COIL program is organized by the Management Department of FEM IPB University in collaboration with the University of Malaysia Sabah. To improve the quality of the program, it is necessary to evaluate the program by analyzing the implementation and evaluating the effectiveness of the program. This study used 59 respondents, as well as using primary data in the form of questionnaires and secondary data in the form of literature studies. The research methods are descriptive analysis, gap analysis, Net Promoter Score and SIPOC diagram. At the reaction level, the participants' perceptions of the program were very high. At the learning level, it shows an increase in participants’ knowledge. At the behavior level, participants are interested in working in the HR field. At the outcome level, the majority of participants recommend the program. Therefore, this program has been running effectively.